2011
DOI: 10.1186/1471-2288-11-116
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and longitudinal validation of the self-reporting questionnaire (SRQ-20) in a Rwandan community setting: a validation study

Abstract: BackgroundThis study took place to enable the measurement of the effects on mental health of a psychosocial intervention in Rwanda. It aimed to establish the capacities of the Self-Reporting Questionnaire (SRQ-20) to screen for mental disorder and to assess symptom change over time in a Rwandan community setting.MethodsThe SRQ-20 was translated into Kinyarwanda in a process of forward and back-translation. SRQ-20 data were collected in a Rwandan setting on 418 respondents; a random subsample of 230 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 38 publications
2
99
0
7
Order By: Relevance
“…Using the cut-off point for ''case-ness'' of 10 or higher recommended by Scholte, et al (2011), the overall prevalence of ''depression'' in this sample was 61.3%, ranging from 47.3% at PHC at MH, to 54.5% at CNC to 77.6% at KYB. That such high levels of depression were detected in this study from a convenience sample of the community suggests a degree of diagnostic misclassification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the cut-off point for ''case-ness'' of 10 or higher recommended by Scholte, et al (2011), the overall prevalence of ''depression'' in this sample was 61.3%, ranging from 47.3% at PHC at MH, to 54.5% at CNC to 77.6% at KYB. That such high levels of depression were detected in this study from a convenience sample of the community suggests a degree of diagnostic misclassification.…”
Section: Resultsmentioning
confidence: 99%
“…Seven or higher is the cut-off for possible depression used by Aidoo and Harpham (2001), but other authors now advocate the use of a different cut-off point. Scholte et al (2011) found that the SRQ-20 performed most reliably as a predictor of CMD in women, in a Rwandan community setting, when the cut-off point was set at 10. In our study, the SRQ-20 results are reported using both the 7 or higher, and the 10 or higher cut-off points, but the cut -off point for participants to proceed to the interview phase was 7 or higher.…”
Section: The Study Designmentioning
confidence: 99%
“…In a study conducted in Rwandan community setting, which analysed the psychometric property and validity of SRQ-20 as screening tool, it was found that the SRQ-20 is highly reliable tool for screening of non-psychotic common mental condition in population. [14] Statistical Analysis SPSS version 15 was used for statistical analysis of data.…”
Section: Srq-20mentioning
confidence: 99%
“…Emotional stress was assessed using a self reporting questionnaire with 20 items (SRQ-20). (9) Respondents were said to experience stress if they answered "Yes" to minimally 6 out of 20 questions in the instrument.…”
Section: Data Collectionmentioning
confidence: 99%